The Auditor and the Firm: A Simple Model of Corporate Cheating and Intermediation - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2005)
We apply a game-theoretic model to the analysis of the recent spate of corporate scandals in which firms have cheated their investors, often with the aid of external auditors. We characterize the different types of equilibria that obtain for different parameter ranges in an auditor’s absence (the parameters we consider being early signal accuracy – a measure of transparency – and withdrawal costs – a measure of the liquidity of investments). We also analyze whether and under what conditions the presence of an informed auditor could lead to an improvement in the sense of honest behavior replacing cheating as the firms’ equilibrium strategy. In doing so we take into account the auditor’s incentives to collude with his clients or extort from them. We use our results to derive some policy predictions including those relating to the Sarbanes-Oxley reforms, and contrast the case of a firm-hired intermediary (like an auditor) with the situation in which an intermediary is hired by investor consortia. Interestingly, we find that mandatory disclosure of audit fees could guarantee honest behavior, in equilibrium, for much of the parameter space in which cheating would have prevailed in an auditor’s absence – as investors are able to check that audit fees lie in a range which removes incentives to cheat for the auditor and his clients. Such disclosure would need to be backed by heavy penalties for false disclosure. We also find that while firm-hired intermediaries have a non-monotone reaction to improvements in public transparency, initially favoring and then opposing them, investor-hired intermediaries unambiguously dislike improvements in public transparency. We argue that frequent rotation of an auditor’s clients may have costs, not just benefits.